Investigation of submicron aerosol characteristics in Changzhou, China: Composition, source, and comparison with co-collected PM2.5. (September 2017) - Ye, Zhaolian; Li, Qing; Liu, Jiashu; Luo, Shipeng; Zhou, Quanfa; Bi, Chenglu; Ma, Shuaishuai; Chen, Yanfang; Chen, Hui; Li, Ling; Ge, Xinlei
Abstract: Mass concentrations and chemical compositions of submicron particles (PM1 ) collected during July 2015 to April 2016 in Changzhou, a city in the Yangtze River Delta region, were systematically investigated for the first time. Specifically, an Aerodyne soot particle aerosol mass spectrometer (SP-AMS) was employed to characterize the water-soluble organic matter (WSOM). The average concentration of PM1 was 63.6 μg m −3, occupying ∼60% of co-collected PM2.5 mass. Water soluble inorganic ions (WSIIs) was the most abundant component with secondary ions (SO4 2−, NO3 − and NH4 + ) as the dominant species. Organic matter (OM) accounted for 21.6% of PM1, with approximately 80% was water-soluble. Trace metals could constitute up to 3.0% of PM1 mass, and Fe, Al and Zn were the three most abundant ones. PAHs were predominated by ones with 5–6 rings, occupying over half of the PAHs mass; further analyses showed that fuel and coal combustion had significant contributions to PAHs. Positive matrix factorization of the WSOM data separated four factors: a traffic-related hydrocarbon-like OA (HOA), a local OA (LOA) likely associated with cooking and coal combustion emissions, etc., a secondary nitrogen-enriched OA (NOA) and an oxygenated OA (OOA). PCA analyses showed that crustal source was likely important for PM1 too. Back trajectory results implied that both PM1 and PM2.5 were mainly derived from local/regional emissions. Our findings present results regarding the PM1 chemistry and its relationship with the PM2.5 in Changzhou, which are valuable for the government to make effective policies to reduce the aerosol pollution in and near the city. Highlights: WSIIs were the largest contributor to PM1 at the study site. SP-AMS was used to characterize the water-soluble organic matter of PM1 . PMF analyses identified traffic, cooking, coal combustion and secondary sources. Pyrogenic emissions were found to contribute significantly to the PAHs.